2017
DOI: 10.3390/nu9050423
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Methyl Donor Supplementation during Gestation Counteracts the Bisphenol A-Induced Impairment of Intestinal Morphology, Disaccharidase Activity, and Nutrient Transporters Gene Expression in Newborn and Weaning Pigs

Abstract: This study was conducted to explore whether exposure to bisphenol A (BPA) during pregnancy could change intestinal digestion and absorption function in offspring using pigs as a model, and whether methyl donor (MET) could counteract the BPA-induced impacts. Fifty Landrace × Yorkshire sows were divided into four dietary groups throughout gestation: control diet (CON); control diet supplemented with BPA (50 mg/kg); control diet supplemented with MET (3 g/kg betaine, 400 mg/kg choline, 150 μg/kg vitamin B12, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
5
19
0
Order By: Relevance
“…Previous studies in humans (Ravelli et al, 1998;Lumey, 1992), rats (Woodall, Johnston, Breier, & Gluckman, 1996), sows (Liu et al, 2017;Wang et al, 2016) and sheep (Sinclair et al, 2007) had found the maternal nutrition during gestation was crucial for postnatal growth or health of the offspring. This was shown to be due, in part, to epigenetic modifications, such as DNA methylation (Lillycrop & Burdge, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans (Ravelli et al, 1998;Lumey, 1992), rats (Woodall, Johnston, Breier, & Gluckman, 1996), sows (Liu et al, 2017;Wang et al, 2016) and sheep (Sinclair et al, 2007) had found the maternal nutrition during gestation was crucial for postnatal growth or health of the offspring. This was shown to be due, in part, to epigenetic modifications, such as DNA methylation (Lillycrop & Burdge, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At high concentrations in the serum pregnant women, Hcy causes the low birth weight of offspring, preterm birth, and intrauterine abortion [179,180]. Maternal dietary supplementation with methyl donors, at doses able to reduce Hcy level in plasma, improved offspring's intestinal digestion and absorption dysfunction induced by BPA, which might be associated with DNA methylation [181].…”
Section: Methyl Donorsmentioning
confidence: 99%
“…DNA methylation is crucial for gene expression regulation, fetal development, and brain function. In the human body, SAMe is synthesized directly from the amino acid methionine in an ATP-driven reaction [55].…”
Section: Gene Expression Changes In Same-exposed Newborn Micementioning
confidence: 99%